Uncover the salt tolerance potential of accessions based on photosynthetic attributes and interaction plot in tomato (Solanum lycopersicum). (17th December 2020) - Rehman, Fazal; Munir, Hassan; Raza, Muhammad A.; Saeed, Asif
Abstract: Soil salinity, being world's gravest and increasing environmental threat, limits the growth and development in nearly all crop plants. The experiment was laid out to investigate the tomato local and exotic germplasm for morpho‐physiological and photosynthetic attributes under salinity stress (0 (control), 8 and 12 dS m −1 ). The phenotype data for morpho‐physiological traits were collected; meanwhile, photosynthetic pigments were analysed also at seedling stage. Analysis of variance, interaction plot, PCV and GCV revealed significantly greater diversity among all accessions for subjecting attributes. Strikingly, principle component analysis (PCA) biplot and cluster heatmap exposed potentially salt tolerant accessions (NAQEEB, BL1076, PBLA1401, 017859, TINY TIM, BL1174, BL1078, PBLA1932, TOMMY TOE, PAKIT and CLN2413) under the highest level of salinity for β‐carotene, lycopene contents, chlorophyll b, carotenoids, pheophytin (b) and total pheophytin. The overall performance of the above‐mentioned accessions was found significant and exhibits tolerant attitude under high salt levels. We suggest that these tolerant accessions might facilitate as a potential source for further breeding programme to improve the agronomically important traits by exploiting both conventional as well as molecular breeding efforts.